A Peculiar Manifestation of Urinary Tract Infection in a 76-year-old Female - Alius Cahyadi; Angelina Yuwono; Nicholas Adrianto; Patricia Michelle Lukito (Indonesian Journal of Tropical and Infectious Disease, 2023)
Purple Urine Bag Syndrome (PUBS) is a rare and benign clinical phenomenon associated with urinary tract infections, characterized by the distinctive purple discoloration of a urinary catheter bag. The underlying cause of PUBS is related to bacterial activity involved in the breakdown of tryptophan, mainly in individuals with predisposing factors such as long-term catheterization, constipation, alkaline urine, and being female. We present the case of a 76-year-old female patient with a history of tuberculous spondylitis who developed PUBS during her hospital stay. The patient had been bedridden for three years and had been given a urinary catheter, which was routinely replaced by a non-medical family member and without a proper antiseptic procedure. A urine culture revealed the presence of Proteus mirabilis, and the patient was treated with intravenous antibiotics while also replacing the urinary catheter and bag. After five days of treatment, the urine bag and catheter remained clear, and the patient was discharged. PUBS is a significant indicator of urinary tract infection, necessitating prompt medical intervention to prevent complications. Healthcare professionals should be aware of this syndrome to enable early detection and appropriate management.